2021
DOI: 10.31234/osf.io/n26fx
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

A meta-analysis of the line bisection task in children

Abstract: Young adults exhibit a subtle, group-level asymmetry of lateral spatial attention favouring the left hemispace over the right (pseudoneglect). We have recently shown that leftward biases are maintained in older adults aged ≥50 when measured using the line bisection task (Learmonth and Papadatou-Pastou 2021). Here we present a meta-analysis of spatial biases in children aged ≤16 years. Databases (PsycINFO, Web of Science, and Scopus) and pre-print servers (bioRxiv, medRxiv, and PsyArXiv) were searched up to 8th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 53 publications
0
3
0
Order By: Relevance
“…The landmark test therefore appears at population level to be independent of the other three tasks, with about 21% of the participants atypical for the landmark task, showing left-hemisphere dominance. The independence of handedness and the landmark (line bisection) tasks in experimental studies (non-fMRI) is also confirmed in meta-analyses in children and in adults [319,320].…”
Section: Associations Between Functional Lateralitiesmentioning
confidence: 58%
“…The landmark test therefore appears at population level to be independent of the other three tasks, with about 21% of the participants atypical for the landmark task, showing left-hemisphere dominance. The independence of handedness and the landmark (line bisection) tasks in experimental studies (non-fMRI) is also confirmed in meta-analyses in children and in adults [319,320].…”
Section: Associations Between Functional Lateralitiesmentioning
confidence: 58%
“…With regards to the elderly, due to the strong heterogeneity of the past studies, it is still difficult to draw any conclusion concerning the suggested weaker leftward bias (Friedrich et al, 2018). What is most likely to be certain is that pseudoneglect exists since childhood (see for a recent meta-analysis Kaul et al, 2021) and seems to remain present throughout an individual's lifespan (see for a recent meta-analysis Learmonth & Papadatou-Pastou, 2022).…”
Section: The Laterality Influencementioning
confidence: 99%
“…The largest set of data comes from studies of what Bowers and Heilman (1980) dubbed "pseudoneglect", a characteristic by which neurologically normal subjects generally make left-sided errors when asked to mark the midpoint of a line. There is an overwhelming and diverse amount of evidence of pseudoneglect in visual line bisection (for reviews, see Friedrich, Hunter, & Elias, 2018;Jewell & McCourt, 2000;Kaul, Papadatou-Pastou, & Learmonth, 2021;Learmonth & Papadatou-Pastou, 2022) and the number of variables that moderate its magnitude is very large, including psychiatric conditions, action video gaming experience, or procedural characteristics of the visual bisection task (see, e.g., Bediou, Adams, Mayer, Tipton, Green, & Bavelier, 2018;Ciricugno, Bartlett, Gwinn, Carragher, & Nicholls, 2021;García-Pérez & Peli, 2014;Latham, Patston, & Tippett, 2014;Ochando & Zago, 2018;Rao, Arasappa, Reddy, Venkatasubramanian, & Reddy, 2015;Ribolsi, Di Lorenzo, Lisi, Niolu, & Siracusano, 2015;Saj, Heiz, Van Calster, & Barisnikov, 2020). We consider all of these data as indirect evidence against the assumption because they only corroborate that respondents intending to mark the midpoint of a line err at doing it, but this body of research does not provide any indication as to whether similar errors occur (and in what direction) when intending to mark alternative positions on the line.…”
mentioning
confidence: 99%